A novel approach for dynamic in-situ surface characterisation of milk protein concentrate hydration and reconstitution using an environmental scanning electron microscope. (November 2020) - Cenini, V.L.; Gallagher, L.; McKerr, G.; McCarthy, N.A.; McSweeney, D.J.; Auty, M.A.E.; O'Hagan, B.M.G.
Abstract: Composition and relative humidity (RH) can have a profound impact on the physical (flowability, stickiness) and functional (reconstitution) properties of milk powder (MP) and therefore its quality, storage stability and shelf-life. Conventional microscopic techniques are not capable of dynamically imaging the effect of RH on MP at high magnification. The aim of this study was to develop a novel method to characterise in-situ and in real time the hydration and reconstitution of five spray-dried milk protein concentrates (MPCs) using an Environmental Scanning Electron Microscope (ESEM). ESEM was employed to observe the surface microstructure of MPC powders with varying protein content (38.63%–80.94%, w/w), at various RH values ranging from 35% to over 100%. MPC powders were imaged by an ESEM without any prior preparation, and with minimal physical sample alteration, thus providing fundamental insights into MPC hydration and reconstitution. ESEM surface analysis showed particle swelling in all MPCs, and that with increasing protein content, hydration and reconstitution efficiency decreased. For the first time, dynamic particle surface fusion was observed. Such fusion can result in stickiness and caking over time. ESEM methods developed here may provide mechanistic insights into the effects of RH during storage. Surface re-arrangement was also observed in all MPCs, but was impeded in MPC70 and MPC80 thus indicating that this is the rate limiting step for MPC reconstitution. This work validates the use of an ESEM to dynamically characterise MPC powder hydration and reconstitution in-situ and in real-time, at both high magnification and spatial resolution. Graphical abstract: Image 1 Highlights: A novel method to image MPC surface during hydration and reconstitution by ESEM. Real-time characterisation of the hydration process at high magnification. Dynamic particle surface fusion and re-arrangement was observed during hydration. At high relative humidity viscous bridges form between particles (fusion). Surface re-arrangement is the rate limiting step for MPC hydration.